Integration of SWOT and AHP Methods to Formulate Marketing Strategy (Case Study : PT. Rattan Craft Indonesia) - Ardi Setiawan; Hana Catur Wahyuni (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2018)
PT. Rattan Craft Indonesia is the p roducers of Wooden indoor Furniture. Rattan Craft does not have the right marketing strategy so that is th e reason the level of sales is not on maximum grade. From the background above, the the problem of this research is: 1. How are the good marketing strategy based on a SWOT method? 2. What a re the good strategy based on AHP. The data analysis in this research using Metod e analysis Swot and AHP. The results of this research get a value of the respective weights by AHP each criterion , namely the ad ministration of 0.057, 0.082 quality, competitive 0.097, 0 .119 raw materials, products already exported 0.151, 0.163 market opportunities, relationships 0.175, 0.156 discipline. The conclusion of this study are: 1. The company utilizes the existing opportunities by maintaining good relations with the relationships that the co mpany's products have been exported can be maintained or even increase exports. 2. The decipline of employees should be more guarded and must be improved so that the company's product quality is maintained.